Investigator-driven randomised controlled trial of cefiderocol vs standard therapy for healthcare associated and hospital acquired Gram-negative bloodstream infection (GAMECHANGER) - Paterson, D. L.; Sulaiman, H.; Po-Yu, L.; Chatfield, M.; Yilmaz, M.; Salmuna, Z. N.; Mazlan, M. Z.; Anunnatsiri, S.; Sirijatuphat, R.; Chotiprasitsakul, D.; Lye, D.; Somani, J.; et al. (Elsevier, 2024)
Background : Cefiderocol has in vitro activity against multi-drug resistant (MDR) and extensively-drug resistant (XDR) gram-negative bacilli. It is FDA- and EMA-approved, but efficacy in bloodstream infections (BSI) is uncertain. We undertook a multicentre, open label, randomised trial comparing cefiderocol with standard of care (SOC) antibiotics in patients with hospital-acquired or healthcare-associated BSI caused by gram-negative bacilli (NCT03869437). Methods: We enrolled adult patients from 17 sites in 6 countries. Participants were randomised <48 hours post initial blood culture collection 1:1 to cefiderocol (2 grams over 3 hours, frequency determined by renal function) or SOC, as determined by the treating team. The primary outcome was all-cause mortality at day 14. Secondary outcomes included 30 and 90-day mortality, clinical and microbiology failure at day 14, microbiological failure up to day 90, colonisation or infection with MD organisms or Clostridioides difficile infection. Our hypothesis was that cefiderocol was non-interior to SOC using a margin of 10% for the primary outcome. Results: 513 patients were enrolled, from 9,144 screened (Figure 1). The main analysis population comprised 504 patients (cefiderocol=250, SOC=254;Figure 1). BSI sources were diverse (UTI 19%, intravascular line-related 18%, intra-abdominal 17%, pneumonia 12%). 59% patients were immunosuppressed, including 21% with haematologic malignancies. 11% BSIs were polymicrobial. The most commonly isolated organisms from index blood cultures were E. coli (in 33% patients), Klebsiella pneumonia (in 30% patients), Pseudomonas spp. (11% patients) and Acinetobacter spp. (8% patients). 121/504 (24%) were infected with >1 carbapenem-resistant isolate, as determined by site microbiology laboratories. 20/250 (8.0%) patients randomized to cefiderocol met the primary outcome of mortality at 14 days. compared with 17/254 (6.7% )randomized to SOC (risk difference 1.3%, 95% CI: 3.2% to 5.9%; RR 1.20 95% CI: 0.64 to 2.23), demonstrating non-inferiority (Table 1, Figure 2). Conclusions: Cefiderocol for hospital-acquired or healthcare-associated gram-negative BSI was non-inferior, but not superior, to SOC.